Rethinking political Islam - Hamid, Shadi, Ed (Oxford University Press, 2017)
The "twin shocks" of the Egyptian coup and the rise of ISIS have challenged conventional wisdom on political Islam, forcing scholars and Muslim activists to reconsider some of the basic assumptions about Sunni Islamist movements. While ISIS and other jihadist groups garner the most media attention, the vast majority of Islamists are of the mainstream variety, seeking gradual change and participating in parliamentary politics when they're allowed to. It is these groups that are the focus of this book. They not only represent the future of what we call "political Islam," but they also - in their own struggles adapting to the changes of recent years - provide a fascinating window into a rapidly changing Middle East. The breadth of the book is expansive, covering the experience of Islamist groups in twelve countries: Egypt, Tunisia, Morocco, Syria, Yemen, Libya, Saudi Arabia, Kuwait, Jordan, and Pakistan, as well as Malaysia and Indonesia. In each of these cases, contributors consider how Muslim Brotherhood and Brotherhood-inspired Islamist movements have grappled with fundamental questions, including gradual versus revolutionary approaches to change, the use of tactical or situational violence, attitudes toward the nation-state, and how ideology and political variables interact. The case studies include authoritarian and democratic states and are not solely focused on the Arab world, allowing readers to consider a greater diversity of Islamist experiences.